Private equity compliance : analyzing conflicts, fees, and risks - Scharfman, Jason A., 1978- (Wiley finance, 2018)
"Develop and manage a private equity compliance program Compliance has become one of the fastest-growing areas in the private equity (PE) space. Mirroring trends from the hedge fund industry, recent surveys indicate that PE managers rank compliance as the single most challenging aspect of their business. Reports also indicate that PE compliance spending has rapidly outpaced other PE operating costs with recent estimates indicating that individual PE funds on average spend at least 15 - 20% of their operating budgets on this area. General Partners (GPs) have also significantly ramped up the hiring of private equity compliance related roles. Private Equity Compliance provides current and practical guidance on key private equity (PE) compliance challenges and trends. Packed with detailed, practical guidance on developing and managing a private equity compliance program, it offers up-to-date case studies and an analysis of critical regulatory enforcement actions on private equity funds in areas including conflict of interest, fees, expenses, LP fun raising disclosures, and valuations. Provides real-world compliance guidance Offers information that is tailored to the current compliance practices employed by GPs in the private equity industry. Provides guidance on managing the compliance risks associated with cybersecurity and information technology risk Serves as a PE-focused complement to the author's previous book, Hedge Fund Compliance If youre a private equity investor or compliance officer looking for trusted guidance on analyzing conflicts, fees, and risks, this is one reference you cant be without"--